Validity Analysis Of Filling And Sealing Bottle In Smart Manufacturing Industry 4.0 (SMI) T201 - Fitria Rahmi; Winda Agustiarmi; Putra Jaya; Yasdinul Huda (Universitas Negeri Padang, 2025)
This research aims to obtain the validity scores for the filling and sealing bottle system that can simulate the filling and sealing process in the industry. The method used in the filling and sealing bottle system is a validity analysis with a quantitative approach. The validity test is conducted to measure the consistency of the measuring instrument against what is intended to be measured, and an instrument is said to be valid performed accurately. The higher the validity of the instrument, the more reliable the data. To obtain the validity score of the filling and sealing bottle system, testing was conducted on the quantity of output at each time using video recordings made 10 times. The test results were scored and validated using the Aiken formula. The validity calculation results showed that tests 1-3 had moderate validity, tests 4-6 had high validity, tests 7 and 8 had moderate validity, and tests 9 and 10 had high validity. The validity analysis results met the standard and produced a validity score of 0.85, which is considered high validity.